Case Studies on Impact of HRM Practices on Organizational Performance in Educational Institutes - Mishra, Angurbala; Biswal, Subhasmita (Journal of Engineering Education Transformations, 2023)
Objective : The study is to address the human resource practices and their direct impact on organizational performance at educational institutes. Methods : This case study was undertaken over six months through a series of visits to the different sites (n=45) in Odisha, India, and a structured questionnaire to assess the whole process of this research. Results : The maximum correlation (r =0.727) has existed between performance appraisal and organizational performance. The highest positive correlation value between performance appraisal and organizational performance in the correlation matrix clarifies that the authorities are required to focus on performance appraisal for fabulous organizational performance.